(untitled) (Journal of Pathology of Nepal, 2021)
Background: In the laboratory, errors can occur at any stage of sample processing; pre-analytical, analytical, and post-analytical. Since the pre-analytical phase is the most common source of laboratory errors, the goal of this study is to identify the types and frequency of pre-analytical errors in the hematology laboratory. Materials and Methods: This is a cross-sectional descriptive study done at Nepal Medical College Teaching hospital for a duration of nine months (January 2020 to September 2020). All blood samples received at the hematology laboratory were included whereas biochemistry and special tests blood samples were excluded. Samples were checked for misidentification (incorrectly labeled vials/vials without labels/incorrectly filled forms), incorrect samples (wrong choice of vials), clotted samples, inadequate samples, diluted samples, hemolyzed samples. The errors that occurred in these samples (both inpatient and outpatient) were noted down and measures were taken accordingly before analyzing the sample. Results: The total number of samples received was 15,337. Pre-analytical errors were seen in 857 samples (5.5%). Inadequate samples (25%) were the most common error followed by incorrect samples (20%), hemolyzed samples (20%), misidentification (14%), clotted samples (12%), and diluted samples (9%). Complete blood count test was most affected. Samples from the inpatient department were most affected. Conclusions: The preanalytical error rate in the hematology unit was 5.5% with an inadequate sample being the commonest error. Most of the errors were seen in the test requested for a complete blood count. Samples from the inpatient department showed the most errors.